The Determinants of Capital Structure of Listed Companies in Developed and Developing Countries: Evidence from Eight Countries - Sun, Shiqi (2019)
This research will discuss the determinants that contribute to capital structure from both the external and internal perspective. Most empirical capital structure determinants are concluded based on data from developed countries. To test whether these factors are generally suitable for different countries, this dissertation chooses 4 developed countries (Australia, Japan, the UK and the USA) and 4 developing countries (Brazil, Russia, India, China, generally known as BRIC block) as research objects. This dissertation will use the panel model to verify the relationship between capital structure and potential determinants. The results show that profitability has the strongest relationship with leverage ratio as it is significant in 6 out of 8 countries., which also indicates the same trend in both non-BRIC and BRIC countries. Size is believed to be the second related variable to leverage as it also has the 6 countries who show reliable relationship of it as profitability. Though the correlation is not identical in these countries, it still has relatively high consistency in BRIC. Consistency of variables in non-BRIC and BRIC can also be found in tangibility and liquidity, whereas the former shows strong positive relationship with the dependent variable and the latter indicates strong negative correlation to leverage ratio. However, the correlation to leverage for growth opportunity is different for non-BRIC and BRIC, it is highly negative in BRIC and less strong but positive in the UK, which is the only related country in non-BRIC.